"Two-pound cookies" or "two pounds of cookies": Children's appreciation of quantity expressions. (2nd October 2017) - Foushee, Ruthe; Falkou, Naoual; Li, Peggy
ABSTRACT: Inspired by Syrett (2013), three experiments explored children's ability to distinguish attributives (e.g., "three-pound strawberries, " where MPs as adjectives signal reference to attributes) versus pseudopartitives (e.g., "three pounds of strawberries, " where MPs combine with of to signal part-whole relations). Given the systematic nature of the syntax-semantics mapping, we asked whether children are able to use syntax to interpret how entities are quantified. In Experiment 1, four- and five-year-olds were asked to choose between two characters for the one who was selling appropriate items matching an attributive or pseudopartitive expression. In Experiment 2, children of the same age heard items described with a phrase using either an attributive, a pseudopartitive, "each" ("each weighs three pounds"), or "all together" ("all together they weigh three pounds"). At test, with some items removed, children were asked whether the same phrase applied to the remaining items (e.g., "Does Dora still have three-pound strawberries ?"). Children did not distinguish between attributives and pseudopartitives but did so for "each" and "all together." Experiment 3 extends the age range with a third experimental design. Children heard "each" or "all together" descriptions (e.g., "each strawberry weighs three pounds") and judged, at test, which of two characters "said it better" (i.e., "Mickey says 'these are two pounds of strawberries, ' but Donald says 'these are two-pound strawberries .'"). Children under 6 were at chance. Together, the three experiments suggest that despite its systematicity, children do not automatically appreciate the mapping between syntax and semantics.